Learning with peers about physical events (Psicologia USP, 2009)
Different play situations that may favor learning and cognitive acquisitions are explored focusing peer interactions among 19-31 month-old children from a socio-interactionist perspective. Play is construed as a privileged space of observation due to its motivational priority for young children. Through play, and/or to play, children use several strategies while trying to solve problems such as introducing him/herself into an already structured social configuration, capturing the partners attention, sorting out conflicts, building up the script of a play episode, reaching a similar result while using a similar object and so on. The present paper aimed to investigate potential forms of learning about physical events when a small group of children deals with objects. Four interactional dynamics were identified to highlight strategies used by children in cooperative actions which carry apparent learning consequences and show that even very young children reflect about his/her and the partners actions. Some theoretical and educational implications of these findings are discussed.